Fixed Drug Eruption in an Epileptic Patient Previously Receiving Treatment With Phenytoin for Seven Years - Keaton S. Smetana; Katie J. Suda PharmD, MS; Leslie A. Hamilton PharmD (SAGE Publishing, 2013)
A 52-year-old African American female presented with severe left thigh pain of unknown etiology. She had a past medical history of generalized seizure disorder treated with phenytoin for 7 years without incident. During admission a nurse witnessed a seizure, and consequently loading and maintenance doses of phenytoin were administered to obtain a therapeutic serum concentration. The patient had a history of noncompliance with multiple subtherapeutic phenytoin levels. Subsequently, unifocal blue discolored spots appeared, progressing to a bullous component that was positive for skin sloughing. Drug-induced fixed drug eruption was diagnosed and attributed to phenytoin. Clinicians should be cognizant of drug-induced fixed drug eruption in patients just initiated and those receiving long-term treatment with phenytoin. The administration rate of phenytoin may be associated with the development of fixed drug eruption.